Impact of Prophylactic Intraoperative Redosing of Antibiotics on the Incidence of Surgical Site Infection in Elective Colorectal Surgery: Results of a Propensity Score-based Analysis - Yozo Suzuki; Masakazu Ikenaga; Kiyotaka Hagihara; Toshiki Noma; Katsunori Matsushita; Naoki Shinno; Masafumi Yamashita; Yoshitomo Yanagimoto; Mitsuyoshi Tei; Junzo Shimizu; Naohiro Tomita; Hiroshi Imamura (Journal of the Anus, Rectum and Colon)
Objectives: This retrospective study was conducted to elucidate the impact of intraoperative redosing of antibiotics (IRA) on the incidence of surgical site infection (SSI) in elective colorectal surgery. Methods: The study involved 61 patient pairs matched 1:1 from among 200 patients who, between April 2019 and December 2020, underwent elective surgery of 180 minutes or longer for colorectal cancer either with or without IRA at our hospital. The incidence of SSI, length of stay after surgery, readmission rate, and reoperation rate were compared between the two groups. Results: No significant between-group difference was found in patient or tumor characteristics or in operative factors. Further, no significant between-group difference was found in the incidence of SSI (with IRA vs. without IRA: 4.9% vs. 4.9%, p=1.000), length of stay after surgery (median 15 [IQR 11-21] days vs. 13 [10-23] days; p=0.302), or reoperation rate (3.3% vs. 0%, p=0.154). No patients in either group were readmitted. Conclusions: The incidence of SSI, length of stay after surgery, and reoperation rate of the without IRA group were comparable to those of the with IRA group in elective surgery of 180 minutes or longer for colorectal cancer.